src/HOL/Semiring_Normalization.thy
author haftmann
Sat May 08 18:52:38 2010 +0200 (2010-05-08)
changeset 36756 c1ae8a0b4265
parent 36753 5cf4e9128f22
child 36845 d778c64fc35d
permissions -rw-r--r--
moved normalization proof tool infrastructure to canonical algebraic classes
haftmann@36751
     1
(*  Title:      HOL/Semiring_Normalization.thy
wenzelm@23252
     2
    Author:     Amine Chaieb, TU Muenchen
wenzelm@23252
     3
*)
wenzelm@23252
     4
haftmann@36751
     5
header {* Semiring normalization *}
haftmann@28402
     6
haftmann@36751
     7
theory Semiring_Normalization
haftmann@36699
     8
imports Numeral_Simprocs Nat_Transfer
wenzelm@23252
     9
uses
haftmann@36753
    10
  "Tools/semiring_normalizer.ML"
wenzelm@23252
    11
begin
wenzelm@23252
    12
haftmann@36756
    13
text {* FIXME prelude *}
haftmann@36756
    14
haftmann@36756
    15
class comm_semiring_1_cancel_norm (*FIXME name*) = comm_semiring_1_cancel +
haftmann@36756
    16
  assumes add_mult_solve: "w * y + x * z = w * z + x * y \<longleftrightarrow> w = x \<or> y = z"
haftmann@36756
    17
haftmann@36756
    18
sublocale idom < comm_semiring_1_cancel_norm
haftmann@36756
    19
proof
haftmann@36756
    20
  fix w x y z
haftmann@36756
    21
  show "w * y + x * z = w * z + x * y \<longleftrightarrow> w = x \<or> y = z"
haftmann@36756
    22
  proof
haftmann@36756
    23
    assume "w * y + x * z = w * z + x * y"
haftmann@36756
    24
    then have "w * y + x * z - w * z - x * y = 0" by (simp add: algebra_simps)
haftmann@36756
    25
    then have "w * (y - z) - x * (y - z) = 0" by (simp add: algebra_simps)
haftmann@36756
    26
    then have "(y - z) * (w - x) = 0" by (simp add: algebra_simps)
haftmann@36756
    27
    then have "y - z = 0 \<or> w - x = 0" by (rule divisors_zero)
haftmann@36756
    28
    then show "w = x \<or> y = z" by auto
haftmann@36756
    29
  qed (auto simp add: add_ac)
haftmann@36756
    30
qed
haftmann@36756
    31
haftmann@36756
    32
instance nat :: comm_semiring_1_cancel_norm
haftmann@36756
    33
proof
haftmann@36756
    34
  fix w x y z :: nat
haftmann@36756
    35
  { assume p: "w * y + x * z = w * z + x * y" and ynz: "y \<noteq> z"
haftmann@36756
    36
    hence "y < z \<or> y > z" by arith
haftmann@36756
    37
    moreover {
haftmann@36756
    38
      assume lt:"y <z" hence "\<exists>k. z = y + k \<and> k > 0" by (rule_tac x="z - y" in exI, auto)
haftmann@36756
    39
      then obtain k where kp: "k>0" and yz:"z = y + k" by blast
haftmann@36756
    40
      from p have "(w * y + x *y) + x*k = (w * y + x*y) + w*k" by (simp add: yz algebra_simps)
haftmann@36756
    41
      hence "x*k = w*k" by simp
haftmann@36756
    42
      hence "w = x" using kp by simp }
haftmann@36756
    43
    moreover {
haftmann@36756
    44
      assume lt: "y >z" hence "\<exists>k. y = z + k \<and> k>0" by (rule_tac x="y - z" in exI, auto)
haftmann@36756
    45
      then obtain k where kp: "k>0" and yz:"y = z + k" by blast
haftmann@36756
    46
      from p have "(w * z + x *z) + w*k = (w * z + x*z) + x*k" by (simp add: yz algebra_simps)
haftmann@36756
    47
      hence "w*k = x*k" by simp
haftmann@36756
    48
      hence "w = x" using kp by simp }
haftmann@36756
    49
    ultimately have "w=x" by blast }
haftmann@36756
    50
  then show "w * y + x * z = w * z + x * y \<longleftrightarrow> w = x \<or> y = z" by auto
haftmann@36756
    51
qed
haftmann@36756
    52
haftmann@36753
    53
setup Semiring_Normalizer.setup
wenzelm@23252
    54
haftmann@36712
    55
locale normalizing_semiring =
wenzelm@23252
    56
  fixes add mul pwr r0 r1
wenzelm@23252
    57
  assumes add_a:"(add x (add y z) = add (add x y) z)"
wenzelm@23252
    58
    and add_c: "add x y = add y x" and add_0:"add r0 x = x"
wenzelm@23252
    59
    and mul_a:"mul x (mul y z) = mul (mul x y) z" and mul_c:"mul x y = mul y x"
wenzelm@23252
    60
    and mul_1:"mul r1 x = x" and  mul_0:"mul r0 x = r0"
wenzelm@23252
    61
    and mul_d:"mul x (add y z) = add (mul x y) (mul x z)"
wenzelm@23252
    62
    and pwr_0:"pwr x 0 = r1" and pwr_Suc:"pwr x (Suc n) = mul x (pwr x n)"
wenzelm@23252
    63
begin
wenzelm@23252
    64
wenzelm@23252
    65
lemma mul_pwr:"mul (pwr x p) (pwr x q) = pwr x (p + q)"
wenzelm@23252
    66
proof (induct p)
wenzelm@23252
    67
  case 0
wenzelm@23252
    68
  then show ?case by (auto simp add: pwr_0 mul_1)
wenzelm@23252
    69
next
wenzelm@23252
    70
  case Suc
wenzelm@23252
    71
  from this [symmetric] show ?case
wenzelm@23252
    72
    by (auto simp add: pwr_Suc mul_1 mul_a)
wenzelm@23252
    73
qed
wenzelm@23252
    74
wenzelm@23252
    75
lemma pwr_mul: "pwr (mul x y) q = mul (pwr x q) (pwr y q)"
wenzelm@23252
    76
proof (induct q arbitrary: x y, auto simp add:pwr_0 pwr_Suc mul_1)
wenzelm@23252
    77
  fix q x y
wenzelm@23252
    78
  assume "\<And>x y. pwr (mul x y) q = mul (pwr x q) (pwr y q)"
wenzelm@23252
    79
  have "mul (mul x y) (mul (pwr x q) (pwr y q)) = mul x (mul y (mul (pwr x q) (pwr y q)))"
wenzelm@23252
    80
    by (simp add: mul_a)
wenzelm@23252
    81
  also have "\<dots> = (mul (mul y (mul (pwr y q) (pwr x q))) x)" by (simp add: mul_c)
wenzelm@23252
    82
  also have "\<dots> = (mul (mul y (pwr y q)) (mul (pwr x q) x))" by (simp add: mul_a)
wenzelm@23252
    83
  finally show "mul (mul x y) (mul (pwr x q) (pwr y q)) =
wenzelm@23252
    84
    mul (mul x (pwr x q)) (mul y (pwr y q))" by (simp add: mul_c)
wenzelm@23252
    85
qed
wenzelm@23252
    86
wenzelm@23252
    87
lemma pwr_pwr: "pwr (pwr x p) q = pwr x (p * q)"
wenzelm@23252
    88
proof (induct p arbitrary: q)
wenzelm@23252
    89
  case 0
wenzelm@23252
    90
  show ?case using pwr_Suc mul_1 pwr_0 by (induct q) auto
wenzelm@23252
    91
next
wenzelm@23252
    92
  case Suc
wenzelm@23252
    93
  thus ?case by (auto simp add: mul_pwr [symmetric] pwr_mul pwr_Suc)
wenzelm@23252
    94
qed
wenzelm@23252
    95
wenzelm@23252
    96
lemma semiring_ops:
wenzelm@23252
    97
  shows "TERM (add x y)" and "TERM (mul x y)" and "TERM (pwr x n)"
wenzelm@28856
    98
    and "TERM r0" and "TERM r1" .
wenzelm@23252
    99
wenzelm@23252
   100
lemma semiring_rules:
wenzelm@23252
   101
  "add (mul a m) (mul b m) = mul (add a b) m"
wenzelm@23252
   102
  "add (mul a m) m = mul (add a r1) m"
wenzelm@23252
   103
  "add m (mul a m) = mul (add a r1) m"
wenzelm@23252
   104
  "add m m = mul (add r1 r1) m"
wenzelm@23252
   105
  "add r0 a = a"
wenzelm@23252
   106
  "add a r0 = a"
wenzelm@23252
   107
  "mul a b = mul b a"
wenzelm@23252
   108
  "mul (add a b) c = add (mul a c) (mul b c)"
wenzelm@23252
   109
  "mul r0 a = r0"
wenzelm@23252
   110
  "mul a r0 = r0"
wenzelm@23252
   111
  "mul r1 a = a"
wenzelm@23252
   112
  "mul a r1 = a"
wenzelm@23252
   113
  "mul (mul lx ly) (mul rx ry) = mul (mul lx rx) (mul ly ry)"
wenzelm@23252
   114
  "mul (mul lx ly) (mul rx ry) = mul lx (mul ly (mul rx ry))"
wenzelm@23252
   115
  "mul (mul lx ly) (mul rx ry) = mul rx (mul (mul lx ly) ry)"
wenzelm@23252
   116
  "mul (mul lx ly) rx = mul (mul lx rx) ly"
wenzelm@23252
   117
  "mul (mul lx ly) rx = mul lx (mul ly rx)"
wenzelm@23252
   118
  "mul lx (mul rx ry) = mul (mul lx rx) ry"
wenzelm@23252
   119
  "mul lx (mul rx ry) = mul rx (mul lx ry)"
wenzelm@23252
   120
  "add (add a b) (add c d) = add (add a c) (add b d)"
wenzelm@23252
   121
  "add (add a b) c = add a (add b c)"
wenzelm@23252
   122
  "add a (add c d) = add c (add a d)"
wenzelm@23252
   123
  "add (add a b) c = add (add a c) b"
wenzelm@23252
   124
  "add a c = add c a"
wenzelm@23252
   125
  "add a (add c d) = add (add a c) d"
wenzelm@23252
   126
  "mul (pwr x p) (pwr x q) = pwr x (p + q)"
wenzelm@23252
   127
  "mul x (pwr x q) = pwr x (Suc q)"
wenzelm@23252
   128
  "mul (pwr x q) x = pwr x (Suc q)"
wenzelm@23252
   129
  "mul x x = pwr x 2"
wenzelm@23252
   130
  "pwr (mul x y) q = mul (pwr x q) (pwr y q)"
wenzelm@23252
   131
  "pwr (pwr x p) q = pwr x (p * q)"
wenzelm@23252
   132
  "pwr x 0 = r1"
wenzelm@23252
   133
  "pwr x 1 = x"
wenzelm@23252
   134
  "mul x (add y z) = add (mul x y) (mul x z)"
wenzelm@23252
   135
  "pwr x (Suc q) = mul x (pwr x q)"
wenzelm@23252
   136
  "pwr x (2*n) = mul (pwr x n) (pwr x n)"
wenzelm@23252
   137
  "pwr x (Suc (2*n)) = mul x (mul (pwr x n) (pwr x n))"
wenzelm@23252
   138
proof -
wenzelm@23252
   139
  show "add (mul a m) (mul b m) = mul (add a b) m" using mul_d mul_c by simp
wenzelm@23252
   140
next show"add (mul a m) m = mul (add a r1) m" using mul_d mul_c mul_1 by simp
wenzelm@23252
   141
next show "add m (mul a m) = mul (add a r1) m" using mul_c mul_d mul_1 add_c by simp
wenzelm@23252
   142
next show "add m m = mul (add r1 r1) m" using mul_c mul_d mul_1 by simp
wenzelm@23252
   143
next show "add r0 a = a" using add_0 by simp
wenzelm@23252
   144
next show "add a r0 = a" using add_0 add_c by simp
wenzelm@23252
   145
next show "mul a b = mul b a" using mul_c by simp
wenzelm@23252
   146
next show "mul (add a b) c = add (mul a c) (mul b c)" using mul_c mul_d by simp
wenzelm@23252
   147
next show "mul r0 a = r0" using mul_0 by simp
wenzelm@23252
   148
next show "mul a r0 = r0" using mul_0 mul_c by simp
wenzelm@23252
   149
next show "mul r1 a = a" using mul_1 by simp
wenzelm@23252
   150
next show "mul a r1 = a" using mul_1 mul_c by simp
wenzelm@23252
   151
next show "mul (mul lx ly) (mul rx ry) = mul (mul lx rx) (mul ly ry)"
wenzelm@23252
   152
    using mul_c mul_a by simp
wenzelm@23252
   153
next show "mul (mul lx ly) (mul rx ry) = mul lx (mul ly (mul rx ry))"
wenzelm@23252
   154
    using mul_a by simp
wenzelm@23252
   155
next
wenzelm@23252
   156
  have "mul (mul lx ly) (mul rx ry) = mul (mul rx ry) (mul lx ly)" by (rule mul_c)
wenzelm@23252
   157
  also have "\<dots> = mul rx (mul ry (mul lx ly))" using mul_a by simp
wenzelm@23252
   158
  finally
wenzelm@23252
   159
  show "mul (mul lx ly) (mul rx ry) = mul rx (mul (mul lx ly) ry)"
wenzelm@23252
   160
    using mul_c by simp
wenzelm@23252
   161
next show "mul (mul lx ly) rx = mul (mul lx rx) ly" using mul_c mul_a by simp
wenzelm@23252
   162
next
wenzelm@23252
   163
  show "mul (mul lx ly) rx = mul lx (mul ly rx)" by (simp add: mul_a)
wenzelm@23252
   164
next show "mul lx (mul rx ry) = mul (mul lx rx) ry" by (simp add: mul_a )
wenzelm@23252
   165
next show "mul lx (mul rx ry) = mul rx (mul lx ry)" by (simp add: mul_a,simp add: mul_c)
wenzelm@23252
   166
next show "add (add a b) (add c d) = add (add a c) (add b d)"
wenzelm@23252
   167
    using add_c add_a by simp
wenzelm@23252
   168
next show "add (add a b) c = add a (add b c)" using add_a by simp
wenzelm@23252
   169
next show "add a (add c d) = add c (add a d)"
wenzelm@23252
   170
    apply (simp add: add_a) by (simp only: add_c)
wenzelm@23252
   171
next show "add (add a b) c = add (add a c) b" using add_a add_c by simp
wenzelm@23252
   172
next show "add a c = add c a" by (rule add_c)
wenzelm@23252
   173
next show "add a (add c d) = add (add a c) d" using add_a by simp
wenzelm@23252
   174
next show "mul (pwr x p) (pwr x q) = pwr x (p + q)" by (rule mul_pwr)
wenzelm@23252
   175
next show "mul x (pwr x q) = pwr x (Suc q)" using pwr_Suc by simp
wenzelm@23252
   176
next show "mul (pwr x q) x = pwr x (Suc q)" using pwr_Suc mul_c by simp
huffman@35216
   177
next show "mul x x = pwr x 2" by (simp add: nat_number' pwr_Suc pwr_0 mul_1 mul_c)
wenzelm@23252
   178
next show "pwr (mul x y) q = mul (pwr x q) (pwr y q)" by (rule pwr_mul)
wenzelm@23252
   179
next show "pwr (pwr x p) q = pwr x (p * q)" by (rule pwr_pwr)
wenzelm@23252
   180
next show "pwr x 0 = r1" using pwr_0 .
huffman@35216
   181
next show "pwr x 1 = x" unfolding One_nat_def by (simp add: nat_number' pwr_Suc pwr_0 mul_1 mul_c)
wenzelm@23252
   182
next show "mul x (add y z) = add (mul x y) (mul x z)" using mul_d by simp
wenzelm@23252
   183
next show "pwr x (Suc q) = mul x (pwr x q)" using pwr_Suc by simp
huffman@35216
   184
next show "pwr x (2 * n) = mul (pwr x n) (pwr x n)" by (simp add: nat_number' mul_pwr)
wenzelm@23252
   185
next show "pwr x (Suc (2 * n)) = mul x (mul (pwr x n) (pwr x n))"
huffman@35216
   186
    by (simp add: nat_number' pwr_Suc mul_pwr)
wenzelm@23252
   187
qed
wenzelm@23252
   188
wenzelm@23252
   189
end
wenzelm@23252
   190
haftmann@36712
   191
sublocale comm_semiring_1
haftmann@36712
   192
  < normalizing!: normalizing_semiring plus times power zero one
haftmann@36712
   193
proof
haftmann@36712
   194
qed (simp_all add: algebra_simps)
wenzelm@23252
   195
haftmann@36756
   196
lemmas (in comm_semiring_1) normalizing_comm_semiring_1_axioms =
haftmann@36756
   197
  comm_semiring_1_axioms [normalizer
haftmann@36756
   198
    semiring ops: normalizing.semiring_ops
haftmann@36756
   199
    semiring rules: normalizing.semiring_rules]
haftmann@36756
   200
haftmann@36756
   201
declaration (in comm_semiring_1)
haftmann@36756
   202
  {* Semiring_Normalizer.semiring_funs @{thm normalizing_comm_semiring_1_axioms} *}
wenzelm@23573
   203
haftmann@36712
   204
locale normalizing_ring = normalizing_semiring +
wenzelm@23252
   205
  fixes sub :: "'a \<Rightarrow> 'a \<Rightarrow> 'a"
wenzelm@23252
   206
    and neg :: "'a \<Rightarrow> 'a"
wenzelm@23252
   207
  assumes neg_mul: "neg x = mul (neg r1) x"
wenzelm@23252
   208
    and sub_add: "sub x y = add x (neg y)"
wenzelm@23252
   209
begin
wenzelm@23252
   210
wenzelm@28856
   211
lemma ring_ops: shows "TERM (sub x y)" and "TERM (neg x)" .
wenzelm@23252
   212
wenzelm@23252
   213
lemmas ring_rules = neg_mul sub_add
wenzelm@23252
   214
wenzelm@23252
   215
end
wenzelm@23252
   216
haftmann@36720
   217
sublocale comm_ring_1
haftmann@36720
   218
  < normalizing!: normalizing_ring plus times power zero one minus uminus
haftmann@36720
   219
proof
haftmann@36720
   220
qed (simp_all add: diff_minus)
wenzelm@23252
   221
haftmann@36756
   222
lemmas (in comm_ring_1) normalizing_comm_ring_1_axioms =
haftmann@36756
   223
  comm_ring_1_axioms [normalizer
haftmann@36756
   224
    semiring ops: normalizing.semiring_ops
haftmann@36756
   225
    semiring rules: normalizing.semiring_rules
haftmann@36756
   226
    ring ops: normalizing.ring_ops
haftmann@36756
   227
    ring rules: normalizing.ring_rules]
chaieb@30866
   228
haftmann@36756
   229
declaration (in comm_ring_1)
haftmann@36756
   230
  {* Semiring_Normalizer.semiring_funs @{thm normalizing_comm_ring_1_axioms} *}
chaieb@23327
   231
haftmann@36712
   232
locale normalizing_semiring_cancel = normalizing_semiring +
wenzelm@23252
   233
  assumes add_cancel: "add (x::'a) y = add x z \<longleftrightarrow> y = z"
wenzelm@23252
   234
  and add_mul_solve: "add (mul w y) (mul x z) =
wenzelm@23252
   235
    add (mul w z) (mul x y) \<longleftrightarrow> w = x \<or> y = z"
wenzelm@23252
   236
begin
wenzelm@23252
   237
wenzelm@23252
   238
lemma noteq_reduce: "a \<noteq> b \<and> c \<noteq> d \<longleftrightarrow> add (mul a c) (mul b d) \<noteq> add (mul a d) (mul b c)"
wenzelm@23252
   239
proof-
wenzelm@23252
   240
  have "a \<noteq> b \<and> c \<noteq> d \<longleftrightarrow> \<not> (a = b \<or> c = d)" by simp
wenzelm@23252
   241
  also have "\<dots> \<longleftrightarrow> add (mul a c) (mul b d) \<noteq> add (mul a d) (mul b c)"
wenzelm@23252
   242
    using add_mul_solve by blast
wenzelm@23252
   243
  finally show "a \<noteq> b \<and> c \<noteq> d \<longleftrightarrow> add (mul a c) (mul b d) \<noteq> add (mul a d) (mul b c)"
wenzelm@23252
   244
    by simp
wenzelm@23252
   245
qed
wenzelm@23252
   246
wenzelm@23252
   247
lemma add_scale_eq_noteq: "\<lbrakk>r \<noteq> r0 ; (a = b) \<and> ~(c = d)\<rbrakk>
wenzelm@23252
   248
  \<Longrightarrow> add a (mul r c) \<noteq> add b (mul r d)"
wenzelm@23252
   249
proof(clarify)
wenzelm@23252
   250
  assume nz: "r\<noteq> r0" and cnd: "c\<noteq>d"
wenzelm@23252
   251
    and eq: "add b (mul r c) = add b (mul r d)"
wenzelm@23252
   252
  hence "mul r c = mul r d" using cnd add_cancel by simp
wenzelm@23252
   253
  hence "add (mul r0 d) (mul r c) = add (mul r0 c) (mul r d)"
wenzelm@23252
   254
    using mul_0 add_cancel by simp
wenzelm@23252
   255
  thus "False" using add_mul_solve nz cnd by simp
wenzelm@23252
   256
qed
wenzelm@23252
   257
chaieb@25250
   258
lemma add_r0_iff: " x = add x a \<longleftrightarrow> a = r0"
chaieb@25250
   259
proof-
chaieb@25250
   260
  have "a = r0 \<longleftrightarrow> add x a = add x r0" by (simp add: add_cancel)
chaieb@25250
   261
  thus "x = add x a \<longleftrightarrow> a = r0" by (auto simp add: add_c add_0)
chaieb@25250
   262
qed
chaieb@25250
   263
haftmann@36756
   264
end
haftmann@36756
   265
haftmann@36756
   266
sublocale comm_semiring_1_cancel_norm
haftmann@36756
   267
  < normalizing!: normalizing_semiring_cancel plus times power zero one
haftmann@36756
   268
proof
haftmann@36756
   269
qed (simp_all add: add_mult_solve)
haftmann@36756
   270
haftmann@36756
   271
declare (in comm_semiring_1_cancel_norm)
haftmann@36756
   272
  normalizing_comm_semiring_1_axioms [normalizer del]
wenzelm@23252
   273
haftmann@36756
   274
lemmas (in comm_semiring_1_cancel_norm)
haftmann@36756
   275
  normalizing_comm_semiring_1_cancel_norm_axioms =
haftmann@36756
   276
  comm_semiring_1_cancel_norm_axioms [normalizer
haftmann@36756
   277
    semiring ops: normalizing.semiring_ops
haftmann@36756
   278
    semiring rules: normalizing.semiring_rules
haftmann@36756
   279
    idom rules: normalizing.noteq_reduce normalizing.add_scale_eq_noteq]
wenzelm@23252
   280
haftmann@36756
   281
declaration (in comm_semiring_1_cancel_norm)
haftmann@36756
   282
  {* Semiring_Normalizer.semiring_funs @{thm normalizing_comm_semiring_1_cancel_norm_axioms} *}
wenzelm@23252
   283
haftmann@36712
   284
locale normalizing_ring_cancel = normalizing_semiring_cancel + normalizing_ring + 
chaieb@25250
   285
  assumes subr0_iff: "sub x y = r0 \<longleftrightarrow> x = y"
wenzelm@23252
   286
haftmann@36720
   287
sublocale idom
haftmann@36720
   288
  < normalizing!: normalizing_ring_cancel plus times power zero one minus uminus
haftmann@36720
   289
proof
haftmann@36756
   290
qed simp
wenzelm@23252
   291
haftmann@36756
   292
declare (in idom) normalizing_comm_ring_1_axioms [normalizer del]
wenzelm@23252
   293
haftmann@36756
   294
lemmas (in idom) normalizing_idom_axioms = idom_axioms [normalizer
haftmann@36756
   295
  semiring ops: normalizing.semiring_ops
haftmann@36756
   296
  semiring rules: normalizing.semiring_rules
haftmann@36756
   297
  ring ops: normalizing.ring_ops
haftmann@36756
   298
  ring rules: normalizing.ring_rules
haftmann@36756
   299
  idom rules: normalizing.noteq_reduce normalizing.add_scale_eq_noteq
haftmann@36756
   300
  ideal rules: normalizing.subr0_iff normalizing.add_r0_iff]
wenzelm@23252
   301
haftmann@36756
   302
declaration (in idom)
haftmann@36756
   303
  {* Semiring_Normalizer.semiring_funs @{thm normalizing_idom_axioms} *}
wenzelm@23252
   304
haftmann@36756
   305
locale normalizing_field = normalizing_ring_cancel +
haftmann@36756
   306
  fixes divide :: "'a \<Rightarrow> 'a \<Rightarrow> 'a"
haftmann@36756
   307
    and inverse:: "'a \<Rightarrow> 'a"
haftmann@36756
   308
  assumes divide_inverse: "divide x y = mul x (inverse y)"
haftmann@36756
   309
     and inverse_divide: "inverse x = divide r1 x"
chaieb@23327
   310
begin
chaieb@23327
   311
haftmann@36756
   312
lemma field_ops: shows "TERM (divide x y)" and "TERM (inverse x)" .
chaieb@23327
   313
haftmann@36756
   314
lemmas field_rules = divide_inverse inverse_divide
wenzelm@26314
   315
chaieb@23327
   316
end
chaieb@23327
   317
haftmann@36720
   318
sublocale field 
haftmann@36756
   319
  < normalizing!: normalizing_field plus times power zero one minus uminus divide inverse
haftmann@36720
   320
proof
haftmann@36720
   321
qed (simp_all add: divide_inverse)
haftmann@28402
   322
haftmann@36756
   323
lemmas (in field) normalizing_field_axioms =
haftmann@36756
   324
  field_axioms [normalizer
haftmann@36756
   325
    semiring ops: normalizing.semiring_ops
haftmann@36756
   326
    semiring rules: normalizing.semiring_rules
haftmann@36756
   327
    ring ops: normalizing.ring_ops
haftmann@36756
   328
    ring rules: normalizing.ring_rules
haftmann@36756
   329
    field ops: normalizing.field_ops
haftmann@36756
   330
    field rules: normalizing.field_rules
haftmann@36756
   331
    idom rules: normalizing.noteq_reduce normalizing.add_scale_eq_noteq
haftmann@36756
   332
    ideal rules: normalizing.subr0_iff normalizing.add_r0_iff]
haftmann@36756
   333
haftmann@36756
   334
declaration (in field)
haftmann@36756
   335
  {* Semiring_Normalizer.field_funs @{thm normalizing_field_axioms} *}
haftmann@28402
   336
haftmann@28402
   337
end